Membrane biogas purification using selective solvents - Буртна, Інеса Анатоліївна; Ружинська, Людмила Іванівна; Гачечіладзе, Отар Отарович; Шафаренко, Микола Васильович; Мурашко, Михайло Михайлович (Eastern-European Journal of Enterprise Technologies, 2013)
Recently, the application of alternative energy resources has acquired significant interest. One of them is biogas. For many industries the production technology of biogas provides cheap disposal of organic wastes. But for its effective use the intensive purification is required. Thus, the separation of a multicomponent gas mixture, containing methane, requires the search of new ways of process implementation, for example, combination of different methods of separation. It is proposed to consider a combination of selective dissolution of methane in liquid absorber with its subsequent release, using membrane pervaporation technology. The choice of the effective selective absorber is based on the calculated dependences for determination of the conditions of equilibrium between liquid and gas phases in the process of absorption of methane and numerical modeling of solubility of the gas mixture components in absorbers. Efficiency of the absorption of methane from the gas mixture depends on the initial concentration of methane in it. To reuse the efficient selective solvent for the absorption process, it is appropriate to clean the solvent using the membrane methods. The article considers the experimental unit for the release of methane from gas mixtures using the efficient selective solvent and pervoporation for the release of the solvent. The method of the process of membrane methane release from biogas was described. The article presents the schematic diagram of installation, maquettes of membrane, absorption and pervoporation devices with the principle of operation.